Left Ventricular Assist Device Malfunctions: It Is More Than Just the Pump. Issue 18 (31st October 2017) - Kormos, Robert L.; McCall, Michael; Althouse, Andrew; Lagazzi, Luigi; Schaub, Richard; Kormos, Michael A.; Zaldonis, Jared A.; Sciortino, Christopher; Lockard, Kathleen; Kuntz, Nicole; Dunn, Elizabeth; Teuteberg, Jeffrey J.
Abstract : Background: Reports of left ventricular assist device (LVAD) malfunction have focused on pump thrombosis. However, the device consists of the pump, driveline, and peripherals, all of which are potentially subject to failure. Methods: Prospectively collected data were reviewed for all LVAD device malfunctions (DMs) occurring in rotary LVADs implanted at a single center between April 2004 and May 2016. Durable LVADs included 108 Heartmate II (HM II) and 105 HeartWare VAD (HVAD). DM data were categorized according to device type and into categories related to the component that failed: (1) controller, (2) peripheral components, and (3) implantable blood pump or its integral electric driveline. Pump-related events were analyzed as pump-specific (suspected or confirmed thrombosis) or nonpump-specific (driveline failure). DM rates were reported as events per 1000 patient-days, and Cox proportional hazard models were used for time-to-event analyses. Cumulative rates of malfunction were examined for the main components of each type of LVAD. Results: Types of DM included controller failure (30%), battery failure (19%), or patient cable failure (14%), whereas only 13% were because of pump failure. DMs were more common in the HM II device (3.73 per 1000 patient-days versus 3.06 per 1000 patient-days for the HVAD, P <0.01). A higher rate of pump-specific malfunctions was discovered in those implanted with an HM II versus an HVAD (0.55 versus 0.39, respectively; P <0.01) and peripheral malfunctions (2.32 versus 1.78 for the HM II and HVAD, respectively; P <0.01); no difference occurred in the incidence of controller DM between the 2 LVADs. Patients with HVAD were 90% free of a pump-specific malfunction at 3 years compared with 56% for the HM II (log-rank P <0.003). Only 74% of the patients with HM II were free of pump thrombosis at 3 years compared with 90% of the patients with HVAD. Freedom from failure of the integrated driveline was 79% at 3 years for the HM II but 100% for the HVAD (log-rank P <0.02). Conclusions: Device malfunction is much broader than pump failure alone and occurs for different components at different rates based on the type of LVAD.